The Position of an Accompanist when Working on the Voice - Xojiyevich, Parpiyev Tursunboy (International Journal on Orange Technologies, 2023)
Instrumental accompaniment is not considered a fixed, conditional component in vocal music. In folklore, many genres are performed without instrumental accompaniment. Instrumental accompaniment is often available in solo performances or in song and dance genres. Professional music, especially choral music, does not have instrumental accompaniment. These include genres of medieval and renaissance music - masses, madrigals, consons, vocal ensembles, acapella.